1996
DOI: 10.1029/96jd00225
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the UARS solar ultraviolet irradiances: Comparison with the ATLAS 1 and 2 measurements

Abstract: The measurements of the solar ultraviolet spectral irradiance made by the two Upper Atmosphere Research Satellite (UARS) solar instruments, Solar Ultraviolet Spectral Irradiance Monitor (SUSIM) and SOLar STellar Irradiance Comparison Experiment (SOLSTICE), are compared with same‐day measurements by two solar instruments on the shuttle ATmospheric Laboratory for Applications and Science (ATLAS) missions, ATLAS SUSIM and Shuttle Solar Backscatter UltraViolet (SSBUV) experiment. These measurements from the four i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(186 citation statements)
references
References 35 publications
(19 reference statements)
8
175
1
2
Order By: Relevance
“…The uncertainties for the SME Lyman (x irradiances are -40% [Rottman, 1981;, and the uncertainties for the AE-E Lyman at irradiances are -30% [Hinteregger et al, 1981]. Whereas, the uncertainty for the UARS Lyman cz irradiance is 5% [Woods et al, 1996]. The SME and AE-E measurements could therefore be adjusted within their respective uncertainty levels to agree with the UARS values.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainties for the SME Lyman (x irradiances are -40% [Rottman, 1981;, and the uncertainties for the AE-E Lyman at irradiances are -30% [Hinteregger et al, 1981]. Whereas, the uncertainty for the UARS Lyman cz irradiance is 5% [Woods et al, 1996]. The SME and AE-E measurements could therefore be adjusted within their respective uncertainty levels to agree with the UARS values.…”
Section: Introductionmentioning
confidence: 99%
“…As described by Thuillier et al (2004), in this wavelength region, the ATLAS composite is based on the average of five datasets (SOL-STICE I, UARS SUSIM, SSBUV, ATLAS SUSIM, and SOLSPEC). Woods et al (1996) compared these datasets for 15 April 1993 and found that the two UARS instruments agreed to about 5%. The average uncertainty of the composite rose to about 10% when ATLAS SUSIM and SSBUV were included.…”
Section: Comparison Of Sim Solstice I and Solstice Ii With Atlas 3 Imentioning
confidence: 99%
“…The overall absolute accuracy of its calibration is valid to about 2% in the 200 to 300 nm range and has a resolution of 0.1 nm with 3 points per resolution element sampling. The UARS SOLSTICE I F-channel instrument (Rottman, Woods, and Sparn, 1993;Woods, Rottman, and Ucker, 1993;Woods et al, 1996) has a SURF II based calibration that is estimated to be accurate to 3% (k = 1). The instrument covers the wavelength range 170 to 315 nm with a resolution of 0.2 nm and a sampling of 3 points per resolution element.…”
Section: Comparison Of Sim Solstice I and Solstice Ii With Atlas 3 Imentioning
confidence: 99%
“…Cebula et al [1994,1996] estimated the agreement between the UARS SUSIM and the SOLSTICE to be +_5% absolute. The measurements made by the two UARS instruments were compared with the same-day measurements by three other solar instruments (the solar spectrum (SOLSPEC), the shuttle solar backscatter ultraviolet (SSBUV), and the shuttle SUSIM instruments) during the ATLAS-1 and ATLAS-2 space shuttle missions in March 1992 and April 1993, respectively [Cebula et al, 1996;Woods et al, 1996], and ATLAS 3 in November 1994. In the 280-400 nm wavelength region, at 0.5 nm spectral resolution, the difference among the various data sets is less than +_3% and is wavelength dependent.…”
Section: Atlas-3 Susim Data Is Shown Inmentioning
confidence: 99%